Pengembangan Alur Layanan Penanggulangan Bencana Banjir terhadap Penyandang Disabilitas di BPBD Barito Kuala: Development of Flood Disaster Management Service Flow for Persons with Disabilities at BPBD Barito Kuala - Dina Roswandi Siregar; Mirnawati Mirnawati; Sakerani Sakerani; Amka Amka (ITScience (Information Technology and Science), 2026)
This research is motivated by the condition of Barito Kuala Regency, which experiences major flooding every year and has a serious impact on vulnerable groups, especially people with disabilities and blindness who have limited mobility. Based on interviews with the Head of the Barito Kuala Regional Disaster Management Agency (BPBD), there is currently no inclusive, disability-friendly disaster management service flow. This problem is exacerbated by the lack of cross-sector collaboration among BPBD, the Social Service, the Health Service, and the Education Service, as well as the absence of a service flow for people with disabilities during disasters. This research uses a qualitative approach, applying the Research and Development (R&D) method for 3D models (Define, Design, Develop), adapted from 4D by Thiagarajan et al. Data sources include BPBD Barito Kuala, the Social Service, the Health Service, lecturers specializing in special education, and people with disabilities and people with blindness. Data collection techniques include interviews, observations, Focus Group Discussions (FGDs), and documentation, while data analysis is conducted both qualitatively and quantitatively. The study's results indicate that the Barito Kuala Regional Disaster Management Agency (BPBD) does not yet have an inclusive disaster management service system; as a result, residents with disabilities are not accommodated during floods. The service flow developed in this study includes three main phases: pre-disaster, during the disaster, and post-disaster, with adjustments to the needs of people with disabilities that were deemed appropriate by three validators, and were assessed as easy to understand, accessible, and appropriate to the needs of people with disabilities according to users. The final product of this study is expected to serve as an operational guideline for the Barito Kuala BPBD in creating an adaptive, equitable, and disability-friendly disaster management system.